Backlash: the undeclared war against American women - Faludi, Susan (Anchor books, 1991)
Keywords: Bibliographie; Nettoyer

Settling Accounts with Subculture: A Feminist Critique - McRobbie, Angela (Feminism and Youth Culture: From ‘Jackie’ to ‘Just Seventeen’, 1991)
Although ‘youth culture’ and the ‘sociology of youth’ — and particularly critical and Marxist perspectives on them — have been central strands in the development of cultural studies over the past fifteen years, the emphasis from the earliest work of the National Deviancy Conference (NDC) onwards has remained consistently on male youth cultural forms.1 There have been studies of the relation of male youth to class and class culture, to the machinery of the State, and to the school, community and workplace. Football has been analysed as a male sport, drinking as a male form of leisure, the law and the police as patriarchal structures concerned with young male (potential) offenders. I do not know of a study that considers, never mind prioritises, youth and the family. This failure by subcultural theorists to dislodge the male connotations of ‘youth’ inevitably poses problems for those who are involved in teaching about those questions. As they cannot use the existing texts ‘straight,’ what other options do they have?
Keywords: Class Culture; Feminist Critique; Moral Panic; Sexual Double Standard; Youth Culture